Sustainability of alternative livelihood strategies in selected sand mining communities in the Ga South Municipality and Gomoa East District of Ghana - Kofi Yeboah Asare; John Victor Mensah; Joseph Boateng Agyenim; Emmanuel Yamoah Tenkorang (Cogent Social Sciences)
In Ghana, terrestrial sand mining in rural and peri-urban areas negatively affects the livelihoods of the majority of the residents employed in land-based livelihoods. We examine the sustainability of the alternative livelihood strategies the residents in these areas adopt as they lose their original livelihoods to sand mining. Both quantitative and qualitative data were collected from 278 household heads and 23 key informants. Descriptive statistics and the chi-square test of independence were employed to analyse the quantitative data, while the qualitative data were analysed thematically. The study revealed that while more than half of the respondents had adopted alternative livelihood strategies as a survival strategy, the remaining household heads were unable to secure alternative livelihoods because of a lack of startup capital, inadequate skills, and the unattractiveness of the alternative livelihood options. Though the adoption of alternative strategies had contributed to improvements in food consumption, employment for some farmers displaced by sand mining, and the resilience of some household heads to handle shocks from sand mining, the strategies were largely unsustainable compared to the residents’ original livelihoods (farming). We recommend that the local government authorities develop policies in consultation with landowners to preserve and restore the original land-based livelihoods of the residents.